Geology, Fluid Inclusion, and H–O–S–Pb Isotope Constraints on the Mineralization of the Xiejiagou Gold Deposit in the Jiaodong Peninsula - Peng Chai; Zeng-qian Hou; Hong-rui Zhang; Lei-lei Dong (Geofluids)
The Xiejiagou deposit is a representative medium-sized gold deposit in Jiaodong the Peninsula, which contains gold reserves of 37.5 t. The orebodies are hosted in the Linglong biotite granite with a zircon LA-ICP-MS U–Pb age of 160.5±1.3 Ma (N=15, MSWD=1.2) and are characterized by disseminated- or stockwork-style ores. Mineralization and alteration are structurally controlled by the NE-striking fault. Three stages of mineralization were identified with the early stage being represented by (K-feldspar) sericite quartz pyrite, the middle stage by quartz gold polymetallic sulfide, and the late stage by quartz carbonate. Ore minerals and gold mainly occurred in the middle stage. Three types of primary fluid inclusions were distinguished in the Xiejiagou deposit, including carbonic-aqueous, pure carbonic, and aqueous inclusions. The primary fluid inclusions of the three stages were mainly homogenized at temperatures of 262–386°C, 192–347°C, and 137–231°C, with salinities of 2.22–8.82, 1.02–11.60, and 1.22–7.72 wt% NaCl equivalent, respectively. These data indicate that the initial ore-forming fluids were a medium temperature, CO2-rich, and low-salinity H2O–CO2–NaCl homogeneous system, and the ore-forming system evolved from a CO2-rich mesothermal fluid into a CO2-poor fluid. Considering the fluid inclusion characteristics, H–O–S–Pb isotopes, and regional geological events, the ore-forming fluid reservoir was likely metamorphic in origin. Trapping pressures of the first two hydrothermal stages estimated from the carbonic aqueous inclusion assemblages were ~224–302 MPa and ~191–258 MPa, respectively. This suggests that the gold mineralization of the Xiejiagou gold deposit occurred at a lithostatic depth of ~7.2–9.7 km. Au(HS)2− was the most probable gold-transporting complex at the Xiejiagou deposit. Precipitation of gold was caused by a CO2 effervescence of initial auriferous fluids.